THE VENTRAL CRANIAL SIZE AND SHAPE VARIATION BETWEEN MALES AND FEMALES OF EUROPEAN BROWN FROGS: RANA DALMATINA, R. GRAECA AND R. TEMPORARIA (ANURA, AMPHIBIA) - Krstičić Račković, Jelena; Tomašević Kolarov, Nataša; Vukov, Tanja (Bulletin of Natural Sciences Research, 2019)
Sexual size and shape dimorphism is a very common phenomenon widely studied in the field of evolutionary biology. The differences between sexes are related to their life strategies and driven by the two evolutionary processes, sexual and natural selection. In amphibians, females are larger sex due to high correlation with fecundity, while dimorphism in body shape is often related to intrasexual competition for opposite sex during the breeding season. The main aim of this study is to describe patterns of ventral cranial size and shape variation between males and females of three species of European brown frogs, Rana dalmatina, R. graeca, R. temporaria, from the Balkan Peninsula. Our results showed that species R. dalmatina and R. graeca are sexually dimorphic for the ventral cranial size while species R. graeca and R. temporaria for the ventral cranial shape. Sexual dimorphism in cranial size is most probably an indirect consequence of natural selection favoring larger body for higher fecundity in explosive breeders like brown frogs. Cranial shape variation is under a strong influence of size variation but without allometric scaling between sexes. Sexual shape differences of analyzed brown frog species were most pronounced in the level of connection between cranium and jaw which indicate that differential diet of males and females can be a factor affecting observed sexual dimorphism patterns. More detailed studies of males and females microhabitats are necessary to conclude if differences in intersexual ecology affect intersexual size and shape differences in the cranium.
Keywords: Cranium; Sexual dimorphism; Geometric morphometrics